Prevalence of virulence genes in Escherichia coli isolates from poultry farms in Northeastern Brazil - Mércia Rodrigues Barros; Mateus Matiuzzi da Costa; Chirles Araújo de França; Jarbas Freitas Amarante; Angélica Liberalino da Silva; José Wilton Pinheiro Júnior; Ana Paula da Silva Ferreira Santos; Rinaldo Aparecido Mota (Ciência Rural)
ABSTRACT: In this study, 35 E. coli isolates obtained from broiler chickens and commercial laying hens from farms in the state of Pernambuco were analyzed. Through PCR analysis, the number of isolates showing amplification for the tested virulence factors were as follows: iss (16), iutA (10), hlyF (18), iroN (11), ompT (16), fimA (14), tsh (5), papA (2), crl (20), csgA (0), and iucA (4). Twenty eight isolates amplified more than one of the tested genes in different patterns, and they were phylogenetically classified into groups A (71.42%) and B1 (28.57%). Thus, the detection of virulence genes in the isolates indicated an association with more significant respiratory conditions and extra-intestinal diseases.